Steroid hormone modulation of RET through two estrogen responsive enhancers in breast cancer - Stine, Zachary E. (Oxford University Press, 2011)
RET, a gene causatively mutated in Hirschsprung disease and cancer, has recently been implicated in breast cancer estrogen (E2) independence and tamoxifen resistance. RET displays both E2 and retinoic acid (RA)-dependent transcriptional modulation in E2-responsive breast cancers. However, the regulatory elements through which the steroid hormone transcriptional regulation of RET is mediated are poorly defined. Recent genome-wide chromatin immunoprecipitation-based studies have identified 10 putative E2 receptor-alpha (ESR1) and RA receptor alpha-binding sites at the RET locus, of which we demonstrate only two (RET −49.8 and RET +32.8) display significant E2 regulatory response when assayed independently in MCF-7 breast cancer cells. We demonstrate that endogenous RET expression and RET −49.8 regulatory activity are cooperatively regulated by E2 and RA in breast cancer cells. We identify key sequences that are required for RET −49.8 and RET +32.8 E2 responsiveness, including motifs known to be bound by ESR1, FOXA1 and TFAP2C. We also report that both RET −49.8 regulatory activity and endogenous RET expression are completely dependent on ESR1 for their (E2)-induction and that ESR1 is sufficient to mediate the E2-induced enhancer activity of RET −49.8 and RET +32.8. Finally, using zebrafish transgenesis, we also demonstrate that RET −49.8 directs reporter expression in the central nervous system and peripheral nervous system consistent with the endogenous ret expression. Taken collectively, these data suggest that RET transcription in breast cancer cells is modulated by E2 via ESR1 acting on multiple elements collectively.